1976
DOI: 10.1111/j.1365-2621.1976.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Pale, Dark and Normal Pork

Abstract: Pale, soft, exudative (PSE), dark cutting, and normal colored pork were compared to determine differences in susceptibility to microbial growth. Chops were packaged and stored under simulated retail conditions. Color, marbling, pH, numbers of total aerobic mesophiles, psychrotrophs, proteolytic and lipolytic bacteria and fluorescent Pseudomonas and incidence of Salm&ella and coagulase positive Staphylococcus were recorded for pork chops as storage time progressed. Data were statistically analyzed. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…Those results were obtained using longissimus dorsi (LD) muscle that had been previously frozen and thawed (F/ T). Although the results agreed with results reported for fresh pork (Rey et al, 1976), F/T treatment of meat has been observed to reduce bacterial populations (Sulzbacher, 1950; Ingram, 1956, 1960;Nassos et al, 1988), extend the lag before bacterial growth (Sulzbacher, 1952;Ingram, 1956, 1960;Rey et al, 1972;Lowry and Gill, 1985) and reduce bacterial growth rate (Sulzbacher, 1952). Despite reported effects of F/r on bacteria, the rate of spoilage development is generally agreed not to greatly differ in fresh or F/ T meat Ingram, 1956, 1960;Jeremiah, 1982;Jul, 1984;Lowry and Gill, 1985;Nassos et al, 1988).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Those results were obtained using longissimus dorsi (LD) muscle that had been previously frozen and thawed (F/ T). Although the results agreed with results reported for fresh pork (Rey et al, 1976), F/T treatment of meat has been observed to reduce bacterial populations (Sulzbacher, 1950; Ingram, 1956, 1960;Nassos et al, 1988), extend the lag before bacterial growth (Sulzbacher, 1952;Ingram, 1956, 1960;Rey et al, 1972;Lowry and Gill, 1985) and reduce bacterial growth rate (Sulzbacher, 1952). Despite reported effects of F/r on bacteria, the rate of spoilage development is generally agreed not to greatly differ in fresh or F/ T meat Ingram, 1956, 1960;Jeremiah, 1982;Jul, 1984;Lowry and Gill, 1985;Nassos et al, 1988).…”
Section: Introductionsupporting
confidence: 85%
“…Thus, for total psychrotrophs, pseudomonads, B. thermosphaca and enterics the bacterial lag phase was longest on PSE pork and shortest on DFD pork in comparison to N. Depending on the bacterium examined, lag phase was 1 to 2 days longer on PSE than DFD pork. Other researchers have also observed that muscle quality can effect duration of the bacterial lag phase (Rey et al, 1976;Newton and Gill, 1978). Few effects of pork muscle quality on the bacterial generation time were statistically significant.…”
Section: Retail Case Lifementioning
confidence: 95%
See 1 more Smart Citation
“…PSE has a low pH, around 5.3-5.6, compared to the normal pH range of 5.6-5.8 (Aberle et al, 2012;Fox, Wolfram, Kemp, & Langlois, 1980). Due to this low pH, there can be fewer microorganisms present compared to normal or DFD pork (Rey et al, 1976). For example, total microorganism load for 8 days at 37°C is log 8 CFU/g for normal pork but only log 4 CFU/g for PSE pork (Fox et al, 1980).…”
Section: Meat Quality and Ultimate Phmentioning
confidence: 99%
“…This increased pH is more favorable for microorganism growth because it is closer to a neutral pH. For example, DFD pork can reach log 5 CFU/cm 2 psychrotrophs while normal pork has log 4 CFU/cm 2 at 5°C for 9 days aerobically (Rey, Kraft, Toppel, Jr., & Hotchkiss, 1976). There is also a lower glycogen concentration in DFD meat because the animal was stressed before slaughter and used those reserves in the stress response.…”
Section: Meat Quality and Ultimate Phmentioning
confidence: 99%